Bahiagrass for Florida Lawns - Laurie Trenholm; Marco Schiavon; J. Bryan Unruh; Travis Shaddox; Kevin E. Kenworthy (EDIS)
Bahiagrass (Paspalum notatum Flugge) was introduced from Brazil in 1914. It was originally used as a pasture grass on the sandy soils of the southeastern United States. Additional varieties have been introduced since that time for use as lawn grasses. Bahiagrass is a low-maintenance lawn grass that does well with limited water and fertilizer inputs. Varieties currently available do not produce a carpet-like, dense lawn like some other warm-season lawn grasses. This publication is intended for homeowners and turfgrass managers that manage bahiagrass in the state of Florida.